The impact of the COVID-19 pandemic on teaching outcomes in higher education - Philipp Hansen; Lennart Struth; Max Thon; Tim Umbach (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
The COVID-19 pandemic forced much of the world to adapt suddenly to severe restrictions. In this study, we attempt to quantify the impact of the pandemic on student performance in higher education. To collect data on important covariates, we conducted a survey among first-year students of Microeconomics at the University of Cologne. In contrast to other studies, we are able to consider a particularly suitable performance measure that was not affected by the COVID-19 restrictions implemented shortly before the start of the summer term 2020. While the average performance improves in the first term affected by the restrictions, this does not apply to students with a low socioeconomic background. Trying to identify more specific channels explaining this finding, interestingly, our data yield no evidence that the average improvement results from the altered teaching formats, suggesting instead that the enhanced performance stems from an increase in available study time.
Keywords: I24; I23; I31; I24; A22; 330; COVID-19; Higher Education; Wellbeing; Education and Inequality; Introductory Economics